Sequential Equilibria in a Ramsey Tax Model - Phelan, Christopher; Stacchetti, Ennio (Econometrica, 2001)
This paper presents a full characterization of the equilibrium value set of a Ramsey tax model. More generally, it develops a dynamic programming method for a class of policy games between the government and a continuum of households. By selectively incorporating Euler conditions into a strategic dynamic programming framework, we wed two technologies that are usually considered competing alternatives, resulting in a substantial simplification of the problem.